1999
DOI: 10.1016/s0092-8674(00)80712-6
|View full text |Cite
|
Sign up to set email alerts
|

A Smad Transcriptional Corepressor

Abstract: Following TGFbeta receptor-mediated phosphorylation and association with Smad4, Smad2 moves into the nucleus, binds to target promoters in association with DNA-binding cofactors, and recruits coactivators such as p300/CBP to activate transcription. We identified the homeodomain protein TGIF as a Smad2-binding protein and a repressor of transcription. A TGFbeta-activated Smad complex can recruit TGIF and histone deacetylases (HDACs) to a Smad target promoter, repressing transcription. Thus, upon entering the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
575
2
11

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(610 citation statements)
references
References 72 publications
17
575
2
11
Order By: Relevance
“…In addition, in vitro studies have demonstrated that TGIF can regulate transforming growth factor-␤ (TGF-␤) -responsive gene expression (Wotton et al, 1999a). TGIF can bind Smads, intracellular components of TGF-␤ signaling Wrana and Attisano, 2000;ten Dijke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in vitro studies have demonstrated that TGIF can regulate transforming growth factor-␤ (TGF-␤) -responsive gene expression (Wotton et al, 1999a). TGIF can bind Smads, intracellular components of TGF-␤ signaling Wrana and Attisano, 2000;ten Dijke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Tgif encodes a homeodomain protein that was originally identified by its ability to bind a retinoid X receptor (RXR) responsive element and inhibit activation of transcription (Bertolino et al, 1995). Subsequent studies disclosed that TGIF contains multiple transcription repression domains and plays an important role as a negative regulator of Activin/TGF-␤ signaling by binding to Smad2 (Wotton et al, 1999a). Briefly, the binding of TGIF to Smad2 leads to the recruitment of general transcription repressors such as histone deacetylases (HDACs) (Wotton et al, 1999a) and Sin3 ) into the Smad2-Smad4 complex.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies disclosed that TGIF contains multiple transcription repression domains and plays an important role as a negative regulator of Activin/TGF-␤ signaling by binding to Smad2 (Wotton et al, 1999a). Briefly, the binding of TGIF to Smad2 leads to the recruitment of general transcription repressors such as histone deacetylases (HDACs) (Wotton et al, 1999a) and Sin3 ) into the Smad2-Smad4 complex. The recruited transcriptional repressors compete out the transcriptional activators, such as p300, and suppress the Smad2-Smad4 mediated transcription (Wotton et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MH1 and MH2, which are separated by a proline-rich linker region of variable length, have distinct functions. The MH2 domain is important for homo-and heteromeric complex formation and for transcriptional activation and repression (Feng et al, 1998;Janknecht et al, 1998;Kawabata et al, 1998;Luo et al, 1999;Wotton et al, 1999). In addition, the MH2 domains of Smad2 and Smad3, but not Smad4, interact with type I receptors (Lo et al, 1998;MacõÂ as-Silva et al, 1996;Zhang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%